Intellectual capital and firm performance: the mediating role of innovation speed and quality. Issue 6 (26th March 2021) - Wang, Zhining; Cai, Shaohan; Liang, Huigang; Wang, Nianxin; Xiang, Erwei
Abstract: The purpose of this study is to explore the influence of intellectual capital (IC) on firm performance, considering the mediating role of innovation speed and quality. We develop a research model based on the IC perspective and innovation literature. We test the model by using structural equation modeling to analyze data collected from 328 high-technology firms in China. The results show that the three components of IC, namely human capital, structural capital, and relational capital, are positively related to innovation speed and quality, which in turn facilitate the operational and financial performance of a firm. The impacts of human and structural capital on financial performance are fully mediated by innovation speed and quality, whereas the impact of relational capital on financial performance is partially mediated. Innovation speed and quality partially mediate the effect of IC on operational performance. As one of the first studies to investigate how IC may influence firm performance through the mediating effects of innovation speed and quality, this study not only contributes to HRM literature on IC and innovation, but also offers managers with insights on how to align their HRM strategies and practices to develop IC when pursuing innovation and performance outcomes.